A STUDY OF THE SOCIAL BEHAVIOR OF NORMAL AND GIFTED STUDENTS STUDYING AT THE SECONDARY LEVEL - Maurya, Dinesh Kumar; Jaiswar, Vikas Kumar (International Journal of Research -GRANTHAALAYAH, 2025)
The present study aimed to compare the social behavior of normal and gifted students studying at the secondary level. A total of 200 students were included in the study, comprising 100 normal students (50 boys and 50 girls) and 100 gifted students (50 boys and 50 girls). A standardized social behavior inventory was used for data collection. The collected data were analyzed using the t-test. The results revealed a statistically significant difference in the social behavior of normal and gifted students, with gifted students exhibiting higher levels of self-control, leadership, and social responsibility. However, no significant difference was found in the social behavior of normal and gifted students based on gender. Based on the study, specific educational suggestions for schools, teachers, and parents have also been provided for the development of social behavior.